The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5005/jp-journals-10024-2225
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Xylitol against Candida albicans: An in vitro Study

Abstract: Aim:The most common fungal infection among human population is candidiasis, the etiology of which is mostly Candida albicans. As a result of a disrupted balance of the normal flora or a compromised immune system, Candida species can become pathogenic. Various in vitro surveys have shown that glucose intake is a promoter of C. albicans growth, whereas in vivo studies have found that xylitol can decrease the risk of candidiasis and angular cheilitis. Hence, we aimed to evaluate for the first time the inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…In addition, prebiotics have demonstrated a direct impact on the host by increasing the secretion of immunoglobulin A (IgA) and stimulating the expression of IL‐10 and IFNs, thereby modulating inflammatory responses against pathogens 111 . The inhibitory properties of prebiotics such as xylitol, xylose, and arabinose on S. mutans and C. albicans have already been documented 112–114 …”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…In addition, prebiotics have demonstrated a direct impact on the host by increasing the secretion of immunoglobulin A (IgA) and stimulating the expression of IL‐10 and IFNs, thereby modulating inflammatory responses against pathogens 111 . The inhibitory properties of prebiotics such as xylitol, xylose, and arabinose on S. mutans and C. albicans have already been documented 112–114 …”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Xylitol also does not appear to affect blood glucose and insulin levels [43][44][45]. Xylitol may also have antimicrobial effect on Candida albicans and can be used as an effective element in gums, toothpastes, and antimicrobial mouthwashes, especially in patients with candidiasis [46]. Therefore, the Streptococcus mutansreducing effect of xylitol-containing SFG is not only of value from an oral health perspective but also potentially for wider general health benefits.…”
Section: Masking Of Participantsmentioning
confidence: 99%
“…Furthermore, a reduction in the fecal level of yeasts was reported, from Log10 9.2–9.4 colony forming units (CFU)/g feces during the control phase to Log10 7.2–7.5 CFU/g feces after xylitol consumption [30]. The type of yeast that was reduced was not reported, but in vitro studies have reported that xylitol can suppress the growth of Candida with a minimal inhibitory concentration of 200 mg/mL and a 99.95% reduction in colony-forming units at 400 mg/mL [31]. Recent mouse studies (5 animals/group) have reported that consumption of xylitol (40 or 194 mg/kg body weight/day) for 15 weeks was associated with an increase in the genus Prevotella , the phyla Eubacteria and Firmicutes and a reduction in the phylum Bacteroidetes by DGGE analysis [32].…”
Section: Digestive Tractmentioning
confidence: 99%